Diagnostic Application of Flexible Cystoscope in Pelvic Fracture Urethral Distraction Defects - Hosseini, Seyed Jalil; Kaviani, Ali; Jabbari, Mohammad; Mohammad Hosseini, Mojtaba; Haji-Mohammadmehdi-Arbab, Amir; Simaei, Navid Reza (Urology Journal, 2009)
Introduction: The aim of this study was to evaluate the diagnostic value of antegrade flexible cystoscopy in pelvic fracture urethral distraction defects (PFUDD). Materials and Methods: Between 1999 and 2004, a total of 111 patients with PFUDD were evaluated by antegrade flexible cystoscopy. The flexible cystoscope was introduced into the posterior urethra and the area was evaluated for any probable fistula, false passages, or displacement of the posterior urethra. For preventing misalignment, flexible cystoscope was also used during the urethroplasty to open the posterior urethra at its exact distal point. Results: Posterior urethra ended distal to the external sphincter in 16 patients (14.4%). Five (4.5%) and 9 (8.1%) patients had severe displacement of the posterior end of the urethra and bladder neck false passage, respectively. Prostatic urethrorectal fistula was detected in 1 patient. Another 1 patient had bladder rhabdomyoma. Conclusion: Flexible cystoscopy is a valuable procedure in the evaluation of the bladder, the bladder neck, and the posterior urethra in patients with urethral distraction defects and complements voiding cystography before the surgery. It is also helpful for showing the exact distal point of the proximal urethra during urethroplasty in cases with displaced posterior urethra.